Shapes of time : history and eschatology in the modernist imagination - McGillen, Michael, 1982- (Signale (Ithaca, N.Y.), 2023)
"The book shows how German-language modernist writers Karl Barth, Franz Rosenzweig, Siegfried Kracauer, and Robert Musil reimagined history and the end of time using the spatial forms of non-Euclidean geometry and modernist mathematics, offering alternatives to the historicist paradigm of linear time guided by teleology"--